THE ANALYSIS OF STUDENTS’ ENVIRONMENTAL-PERCEIVED SCIENTIFIC ATTITUDES THROUGH THE ROLE OF PARENTS AND TEACHERS - Septian Airlanda, Gamaliel (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Modern technology causes environmental problems and climate change. An eco-friendly school becomes one of the solutions to that problem in Indonesia. However, the program has not been effective for society to change their attitude and behavior. This research aims to find an appropriate solution using several steps; to analyze students’ scientific attitude and environmental knowledge; to analyze the role of teacher and parents; and to formulate an action to increase students’ scientific attitude. This descriptive qualitative research results on students’ scientific attitude that changes the behavior in daily life, measured by using a particular indicator. This needs cooperation between teachers and parents to support changes in students' characters.